A statistical quality study on Splash Corporation - Atuli, Marian L.; Balba, Karen Ann M.; Collado, Hazel Kristine M. (Diliman, Quezon City College of Engineering, 2005)
This is a statistical quality control study conducted on Splash Corporation, one of the leading manufacturers in the personal care industry. With the company's goals directed towards providing consumers with products that can very well compete with multinational companies, quality has always been very important to the company. The study was made on Biolink Facial scrub, a product that has entered the market only recently. The product was chosen as it is believed that improvements on the processes involved in its manufacture can at a large extent enhance its market performance. Since success in competition can be best achieved by quality improvement, quality parameters critical to the product are examined. Data revealed that among the quality parameters, specific gravity, is the characteristic which the production department finds difficult to control. Out of the 49 batches of scrub produced, 95.8 percent have specific gravity values that are outside the specifications. Specifically, the values obtained are lower than the lower specification limit set. It was found that the problem in specific gravity results from the bubbly consistency of the scrub produced. X and MR control charts constructed for the process showed that previous attempts to make specific gravity conform by changing the mixing speed used in the process does not affect the results. It was, however, interestingly noted that when the compounder lowered the vacuum pressure used when transferring the semi-finished scrubs from the kettles into the mixing tank, an increase in the values have transpired. Though the action done did not make the values conform, the improvement in the specific gravity values were significant. This had become the basis of the group to recommend the design of an experiment aimed at determining the right vacuum pressure to use. Since lowering the pressure resulted to higher specific gravity values and since the 19 mm Hg pressure used was based on the compounder's judgment alone, the group suggests testing 12, 15, and 17 mm hg pressure. The use of one of the mentioned pressures should be ordered once the results of the experiment would show conformance to specifications.Another major problem identified is the defects on the packaging materials supplied. Delays in packaging have occurred since the materials that have already been accepted by the QC department are later found to be defective and must therefore be remedied before use. From interviews conducted, it was found that this problem occurs because the inspection procedure is done without randomization. From the given data, it was also observed that display boxes have the greatest share in the nonconforming materials supplied. The most common defects encountered for this material are over glue, off color and grain direction defects. The mentioned accounts for 69.44 percent of the defects seen in the said packaging supply. It was traced that much of the off colored display boxes are coming from C itiprint. Those of wrong grain direction are primarily from Quiapo and over glued display boxes are from Speed Master. Information such as this must be relayed to the suppliers so that the latter can do something about their processes. This is beneficial to both parties. The company can be better assured of good quality materials once the supplier's processes are improved. It is also recommended that management must conduct individual SPC of their suppliers so that they can detect shifts in the supplier's processes over time. Doing SPC can also give them a lot of information about their supplier's capability to provide materials of good quality. With the recommendation stated the group hopes to be able to share something in the company's continual search for improvements.
Feasibility study
Submitted in partial fulfillment of the course requirements in IE 135 : Industrial Quality Control
Keywords: Splash Corporation; Cosmetics industry; Quality control